Organs-on-Chips with combined multi-electrode array and transepithelial electrical resistance measurement capabilities. Issue 13 (13th June 2017) - Maoz, Ben M.; Herland, Anna; Henry, Olivier Y. F.; Leineweber, William D.; Yadid, Moran; Doyle, John; Mannix, Robert; Kujala, Ville J.; FitzGerald, Edward A.; Parker, Kevin Kit; Ingber, Donald E.
Abstract : Combined integration of TEER and MEA sensors in a single endothelialized Organ-on-Chip platform. Abstract : Here we demonstrate that microfluidic cell culture devices, known as Organs-on-a-Chips can be fabricated with multifunctional, real-time, sensing capabilities by integrating both multi-electrode arrays (MEAs) and electrodes for transepithelial electrical resistance (TEER) measurements into the chips during their fabrication. To prove proof-of-concept, simultaneous measurements of cellular electrical activity and tissue barrier function were carried out in a dual channel, endothelialized, heart-on-a-chip device containing human cardiomyocytes and a channel-separating porous membrane covered with a primary human endothelial cell monolayer. These studies confirmed that the TEER–MEA chip can be used to simultaneously detect dynamic alterations of vascular permeability and cardiac function in the same chip when challenged with the inflammatory stimulus tumor necrosis factor alpha (TNF-α) or the cardiac targeting drug isoproterenol. Thus, this Organ Chip with integrated sensing capability may prove useful for real-time assessment of biological functions, as well as response to therapeutics.